Antisocial Behavior and Interpersonal Values in High School Students - Molero Jurado, María del Mar; Pérez Fuentes, María del Carmen; Carrión Martínez, José J.; Luque de la Rosa, Antonio; Garzón Fernández, Anabella; Martos Martínez, África; Simón Márquez, Maria del Mar; Barragán Martín, Ana B.; Gázquez Linares, José J. (Frontiers in Psychology, 2017)
This article analyzes the characteristics of antisocial behavior and interpersonal values of high school students (Compulsory Secondary Education) (CSE), the profile of students with high levels of antisocial behavior with regard to interpersonal values, and possible protection from antisocial behavior that interpersonal values could provide. The Interpersonal Values Questionnaire (IVQ) was used to assess interpersonal values, and the Antisocial-Delinquent (A-D) Behaviors Questionnaire was employed to assess antisocial behaviors. The sample was made up of 885 CSE students aged 14-17. The results revealed a greater prevalence of antisocial behaviors among males and fourth-year CSE students. Moreover, antisocial behaviors were more frequent among participants with high scores in Stimulation, Recognition, Independence, and Leadership and low scores in Conformity and Benevolence. Lastly, logistic regression analyses showed that low scores in Conformity and Benevolence and high scores in Independence predicted high scores in antisocial behavior. The possibility of identifying certain interpersonal values which could positively or negatively affect the appearance of antisocial behavior during adolescence is discussed.